α-Glucosidase inhibitory activity and cytotoxic effects of some cyclic urea and carbamate derivatives - Jelena B. Popović-Djordjević; Ivana I. Jevtić; Nadja Dj Grozdanić; Sandra B. Šegan; Mario V. Zlatović; Milovan D. Ivanović; Tatjana P. Stanojković (Taylor & Francis Group, 2017)
The inhibitory activities of selected cyclic urea and carbamate derivatives (1-13) toward α-glucosidase (α-Gls) in in vitro assay were examined in this study. All examined compounds showed higher inhibitory activity (IC50) against α-Gls compared to standard antidiabetic drug acarbose. The most potent was benzyl (3,4,5-trimethoxyphenyl)carbamate (12) with IC50 = 49.85 ± 0.10 µM. In vitro cytotoxicity of the investigated compounds was tested on three human cancer cell lines HeLa, A549 and MDA-MB-453 using MTT assay. The best antitumour activity was achieved with compound 2 (trans-5-phenethyl-1-phenylhexahydro-1H-imidazo[4,5-c]pyridin-2(3H)-one) against MDA-MB-453 human breast cancer cell line (IC50 = 83.41 ± 1.60 µM). Cyclic ureas and carbamates showed promising anti-α-glucosidase activity and should be further tested as potential antidiabetic drugs. The PLS model of preliminary QSAR study indicated that, in planing the future synthesis of more potent compounds, the newly designed should have the substituents capable of polar interactions with receptor sites in various positions, while avoiding the increase of their lipophilicity.